1994
DOI: 10.1001/archsurg.1994.01420340105021
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Evaluation of Abnormal Mammographic Findings to Avoid Unnecessary Breast Biopsies

Abstract: Rigorous mammographic evaluation and the use of stereotactic biopsy for selected lesions can prevent breast biopsy for low-suspicion mammographic abnormalities while still allowing the detection of early-stage breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…16 The nuclear features are sufficiently discriminatory for separating benign and malignant lesions. However, the existence of cytological findings that discriminate between ductal carcinoma in situ and invasive ductal carcinoma has not been unanimously accepted.…”
Section: Discussionmentioning
confidence: 99%
“…16 The nuclear features are sufficiently discriminatory for separating benign and malignant lesions. However, the existence of cytological findings that discriminate between ductal carcinoma in situ and invasive ductal carcinoma has not been unanimously accepted.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4] For the mammographic category IV final assessment, the PPV is reported to be 30 -34%. 5,6 In our study sample, the PPV of BI-RADS category IV was 28.9%.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that the positive predictive value (PPV) for biopsies performed because of mammographic findings is 15-40%. [2][3][4] For the category IV final assessment, the PPV is reported to be 30 -34%. 5,6 This high rate of false-positive mammograms results in a correspondingly high rate of unnecessary biopsies that impose a heavy psychologic burden on women and a heavy financial cost on the health care system.…”
mentioning
confidence: 99%
“…Because of the high index of suspicion of these lesions, some clinicians recommend an open biopsy to obtain a definitive diagnosis, because a nondiagnostic reading of a stereotactic core biopsy would not avoid the need for a subsequent open biopsy. [11][12][13] Our study, as well as reports by others, suggests that there are several reasons why stereotactic core biopsy may be advantageous for even the highly suspicious lesions. 9 -14 From the cost standpoint, Yim et al 1 and Whittin et al 15 have reported that stereotactic core biopsy reduced the number of surgical procedures performed per patient.…”
Section: Discussionmentioning
confidence: 57%